Eccentric compressive behavior of steel fiber-reinforced RC columns strengthened with CFRP wraps: Experimental investigation and analytical modeling. (1st January 2021) - Nematzadeh, Mahdi; Mousavimehr, Mehdi; Shayanfar, Javad; Omidalizadeh, Meysam
Highlights: Eccentric behavior of steel fiber-reinforced concrete columns strengthened with CFRP wraps was studied. CFRP sheets improved the loading capacity and ductility of RC columns. Steel fibers affected loading capacity of RC columns negligibly but made them more ductile. Eccentricity loading mitigated the effect of confinement with CFRP sheets on reinforced concrete strength. Proposed model considers simultaneous effects of confinement with CFRP sheets and transverse reinforcement. Abstract: Today, one of the most commonly used retrofitting techniques for reinforced concrete (RC) columns for enhancing their structural performance is to externally confine these columns with carbon fiber-reinforced polymers (CFRPs). From another aspect, the presence of steel fibers in the concrete mixture enhances the behavior of structural members. In this research, the eccentric compressive behavior of steel fiber-reinforced concrete columns strengthened with CFRP wraps, which has remained mainly under-researched, is explored experimentally and analytically. For that end, eighteen RC columns with plain concrete and fiber-reinforced concrete, confined and unconfined with CFRP sheets, length to width ratios ( L/h ) of 4.2 and 8.3, and load eccentricity ratios ( e/h ) of 0.29, 0.46, and 0.63 were manufactured and tested under eccentric compressive loading. The findings indicated that the CFRP sheets improved the loading capacity and ductility of the RC columns, while the presence of steel fibers in the concrete affected the loading capacity of the columns negligibly but made them more ductile. Further, the eccentricity of the applied load mitigated the effect of confinement with CFRP sheets on the reinforced concrete strength. Regarding the significance of the performance of these columns, an analytical model with the purpose of predicting the behavior of fibrous RC concrete columns strengthened with CFRP sheets under an eccentric compressive load was developed. In this model, by considering the simultaneous effects of the confinement with CFRP sheets and transverse reinforcement, the moment–curvature and the load–deflection diagrams were determined using the fiber section analysis method. Assessing the analytical findings against the experimental ones of the present work and those of others indicated that the proposed model is able to properly predict the behavior of fibrous concrete columns confined with transverse reinforcement and CFRP sheets under eccentric compressive loading.